Process for the production of diacylglycerol - Lai, Oi Ming; Yusof, Mohd. Suria Affandi; Lo, Seong Koon; Long, Kamariah; Tan, Chin Ping; Lim, Jew Yeok; Taharuddin, Shawaluddin; Hashim, Khairudin (2011)

(untitled)
This invention relates to a method for producing DAG. Suitable palm-based starting materials will be used to produce products such as ?healthy? cocoa butter-like DAG to be used in the production of healthy chocolate for the growing diet-conscious consumers as well as margarine/shortening. In this project too, a different approach for the manufacturing of MLCT oil has been developed. A food grade chemical catalysts that can be regenerated for use again will be used besides the enzymic catalysts to produce both DG and MLCT oil.